Collateral easing and safe asset scarcity: How money markets benefit from low-quality collateral - Stefan Greppmair; Karol Paludkiewicz; Sascha Steffen (Deutsche Bundesbank, 2025)
We show that central bank lending against lower quality collateral can improve conditions in the repo market. For identification we take advantage of a pandemic- related temporary extension of the collateral framework of the European Central Bank (ECB), which allows banks to pledge previously ineligible credit claims as collateral for refinancing operations. We use a difference-in-differences approach and exploit banks that do not mobilize credit claims ex ante as a control group. We find that banks affected by the temporary extension pledge newly eligible credit claims in order to reduce the encumbrance of high-quality marketable assets. Treated banks lend out these marketable assets as collateral in the repo market, which helps to alleviate asset scarcity.
Keywords: E43; E44; E58; G21; 330; asset scarcity; money markets; monetary policy; collateral framework